The Arctic Cylindrocystis (Zygnematophyceae, Streptophyta) Green Algae are Genetically and Morphologically Diverse and Exhibit Effective Accumulation of Polyphosphate - Barcytė, Dovilė; Pilátová, Jana; Mojzeš, Peter; Nedbalová, Linda (Journal of phycology, 2020)
The green algal genus Cylindrocystis is widespread in various types of environments, including extreme habitats. However, very little is known about its diversity, especially in polar regions. In the present study, we isolated seven new Cylindrocystis-like strains from terrestrial and freshwater habitats in Svalbard (High Arctic). We aimed to compare the new isolates on a molecular (rbcL and 18S rDNA), morphological (light and confocal laser scanning microscopy), and cytological (Raman microscopy) basis. Our results demonstrated that the Arctic Cylindrocystis were not of a monophyletic origin and that the studied strains clustered within two clades (tentatively named the soil and freshwater/glacier clades) and four separate lineages. Morphological data (cell size, shape, and chloroplast morphology) supported the presence of several distinct taxa among the new isolates. Moreover, the results showed that the Arctic Cylindrocystis strains were closely related to strains originating from the temperate zone, indicating high ecological versatility and successful long-distance dispersal of the genus. Large amounts of inorganic polyphosphate (polyP) grains were detected within the chloroplasts of the cultured Arctic Cylindrocystis strains, suggesting effective luxury uptake of phosphorus. Additionally, various intracellular structures were identified using Raman microscopy and cytochemical and fluorescent staining. This study represents the first attempt to combine molecular, morphological, ecological, and biogeographical data for Arctic Cylindrocystis. Our novel cytological observations partially explain the success of Cylindrocystis-like microalgae in polar regions.
Keywords: Arktida; Arctic Regions; fluorescent staining; phylogeny; Phylogeny; Cylindrocystis; Raman microscopy; toluidine blue; Chlorophyta; fylogeneze; Svalbard; morphology; polar habitats; ecology; diversity; Streptophyta; polyfosfáty; Polyphosphates